PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2017 - Maulidizen, Ahmad; Nabila, Nida (Jurnal Penelitian, 2019)
The development of the Indonesian economy is inseparable from the rapid development of the banking sector, including Islamic banking. This will cause competition between banks to be even tighter to increase competitiveness in various sectors, including the level of profitability. However, the profitability of Sharia Commercial Banks is still low, which is below the standard set by Bank Indonesia of 1.5%. This study aims to describe the description of murabahah financing and profitability, as well as verify the effect of murabahah financing on profitability in sharia commercial banks in Indonesia. Profitability is measured using Return On Assets (ROA) and murabahah financing measured by net murabahah financing on the financial statements of each bank. The research method used is descriptive and verification method. The number of samples used in this study were 72 observational data from 9 Islamic Commercial Banks in Indonesia during the period 2010-2017. The results of this study murabahah financing have a positive and significant effect on the profitability of Islamic Commercial Banks in Indonesia